An Early Shoulder Repositioning Program in Birth-Related Brachial Plexus Injury: A Pilot Study of the Sup-ER Protocol. (June 2014) - Verchere, Cynthia; Durlacher, Kim; Bellows, Doria; Pike, Jeffrey; Bucevska, Marija
Background: Birth-related brachial plexus injury (BRBPI) occurs in 1.2/1, 000 births in British Columbia. Even in children with "good" recovery, external rotation (ER) and supination (Sup) are often weaker, and permanent skeletal imbalance ensues. A preventive early infant shoulder passive repositioning program was created using primarily a novel custom splint holding the affected arm in full ER and Sup: the Sup-ER splint. The details of the splint and the shoulder repositioning program evolved with experience over several years. This study reviews the first 4 years. Methods: A retrospective review of BCCH patients managed with the Sup-ER protocol from 2008 to 2011 compared their recovery scores to matched historical controls selected from our database by two independent reviewers. Results: The protocol was initiated in 18 children during the study period. Six were excluded due to the following: insufficient data points, non-compliance, late splint initiation, and loss to follow-up. Of the 12 matches, the Sup-ER group final score at 2 years was better than controls by 1.18 active movement scale (AMS) points ( p =0.036) in Sup and 0.96 AMS points in ER (but not statistically significant ( p =0.13)). Unexpectedly, but importantly, during the study period, zero subjects were assessed to have the active functional criteria to indicate brachial plexus reconstruction, where previously we operated on 13 %. Conclusions: Early application of passive shoulder repositioning into Sup and ER may improve outcomes in function of the arm in infants with BRBPI. A North American multi-site randomized control trial has been approved and has started recruitment.